Pemodelan Pengaruh Pentahelix Terhadap Peningkatan Nilai pada UPT Pengembangan Agribisnis Tanaman Pangan dan Hortikultura Provinsi Jawa Timur - Nugroho, Tofan Tri; Karima, Tsabita; Hidayat, Anastasya Putri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The agribusiness sector is one of the most important sectors in Indonesia. Therefore, simultaneous efforts are needed to be able to continue to grow this sector. This study aims to identify the role of actors in Pentahelix in increasing the value of the agribusiness sector, especially at the UPT Agribusiness Development of Food Crops and Horticulture at the Agriculture and Food Security Office of East Java Province. The research method used is descriptive qualitative research using the pentahelix approach and Porter's value chain analysis. The result of this study is the formation of a matrix model of the influence of pentahelix-value chain analysis (PVCA) at the UPT Development of Food Crops and Horticulture Agribusiness at the Agriculture and Food Security Service of East Java Province. The actor with the biggest role in increasing the institution's value is academia, while the party with the smallest influence is the media.